Digital Transformation and The Blue Economy: Penta-Helix Model For Catfish Farmers In West Java - Havidz, Ikramina Larasati Hazrati; Wiratih, Hernawati W. Retno; Aima, M. Havidz; Amin, Grace; Santowijaya, Alfadli (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the impact of digital transformation in increasing the income of catfish farmers in several ways: (1) Analyze who benefits from the implementation of digital transformation; (2) Analyze the creation of jobs with the use of digital transformation; (3) Analyze the motivation of catfish farmer groups in entrepreneurship; (4) Analyze the use of digital transformation in the implementation of the blue economy. Qualitative methods were used to collect initial data related to the potential of catfish farmers in West Java Province, Indonesia. Participatory observation, in-depth interviews, surveys, and Penta-Helix model were also utilized. This study also formulates hypotheses and builds instruments for quantitative measurement. Our research focus on one province which may not generalizable to other cities and provinces in Indonesia. The future research may conduct in other cities or provinces because Indonesia is well known as archipelagic country in the world that has great potential for blue economy in the marine and fisheries sector. West Java proximity to Jakarta provides a logistical advantage for catfish distribution. A penta-helix collaboration (government, stakeholders, academia, community, industry) should develop infrastructure for cultivation, processing, logistics and digital management.